(untitled) (Training and Practice : Journal of Educational Sciences, 2019)
The change of the role of the (special)education teacher means a challenge for every person of the profession. However, it is extremely important that there are milestones which provide safety beside the changes, even if they experience changes themselves. Such reference point for special education teachers participating in the diagnostic procedure is the diagnostic protocol, which standardizes special education diagnostics in the area of our country. It has defined the selection of the topic of my research: what the experts of a particular region think of the application of diagnostic protocol. The research result throws light on the fact that diagnostic protocol is determinant in the diagnostic process. The discovered components and connections confirm the importance and demand for standardization, organization and team work.